Painting of Haydn's house by Joseph von Mayenberg - Mayenberg, Joseph von (artist)::::::::::::::: (2023)
Original watercolor painting of Joseph Haydn's birth house in Rohrau, Austria, artist unknown. Another copy is at the Gesellschaft der Musikfreunde according to the catalog record for a photograph at the Beethoven-Haus (NE 81, Band VII, Nr. 1229 a). Inscribed on verso: In diesen Hause zu Rohrau wird Hayden am 31. März gebornen. With additional sheet inscribed with quotation from Ferdinand Hiller's "Tonleben" regarding Beethoven's copy of the painting (with translation).